2022
DOI: 10.3390/antiox11010152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of MnSOD Modify the Impacts of Environmental Melamine on Oxidative Stress and Early Kidney Injury in Calcium Urolithiasis Patients

Abstract: Environmental melamine exposure increases the risks of oxidative stress and early kidney injury. Manganese superoxide dismutase (MnSOD), glutathione peroxidase, and catalase can protect the kidneys against oxidative stress and maintain normal function. We evaluated whether their single-nucleotide polymorphisms (SNPs) could modify melamine’s effects. A total of 302 patients diagnosed with calcium urolithiasis were enrolled. All patients provided one-spot overnight urine samples to measure their melamine levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Guo et al showed that melamine activates the NF-κB/cox-2 and NOX/ROS pathways that induce inflammation and oxidative stress highlighting the significant role of NOX in melamine-induced ROS formation [ 5 ]. A recent study showed the effect of single-nucleotide polymorphisms (SNPs) in Manganese superoxide dismutase (MnSOD) enzyme which could modify the protective response of antioxidant enzyme toward melamine induced oxidative stress and increases the risk of renal tubular injury in calcium urolithiasis patients [ 6 ]. Another study investigated the effects of melamine containing diets on the various parameters of Oreochromisniloticus and showed that melamine significantly reduced the activity of superoxide dismutase and glutathione peroxidase [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al showed that melamine activates the NF-κB/cox-2 and NOX/ROS pathways that induce inflammation and oxidative stress highlighting the significant role of NOX in melamine-induced ROS formation [ 5 ]. A recent study showed the effect of single-nucleotide polymorphisms (SNPs) in Manganese superoxide dismutase (MnSOD) enzyme which could modify the protective response of antioxidant enzyme toward melamine induced oxidative stress and increases the risk of renal tubular injury in calcium urolithiasis patients [ 6 ]. Another study investigated the effects of melamine containing diets on the various parameters of Oreochromisniloticus and showed that melamine significantly reduced the activity of superoxide dismutase and glutathione peroxidase [ 7 ].…”
Section: Introductionmentioning
confidence: 99%